PROSES AKTIVASI ARANG AKTIF DARI CANGKANG KEMIRI (Aleurites moluccana) DENGAN VARIASI JENIS DAN KONSENTRASI AKTIVATOR KIMIA - Gusti Gilang Ramadhan Maulana; Lya Agustina; Susi Susi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
Candlenut (Aleurites moluccana) is one of commodities widely grown in indonesia and undergo development production a rapid progress .Production plantation the people plants candlenut in 2014 reached 107,3 thousand tons (bps, 2014). Charcoal active are carbon already activated so pores open so retention is greater than the charcoal ordinary .The purpose of this research is to determine variety of and concentration activator chemical the best in the process activation so that can improve the quality of the active charcoal shells fruit candlenut produced. Design experiments used in in this research is a random a group (a shelf ) consisting of 2 factors , namely factors 1 is the type activator chemical ( j ) and factors 2 is the concentration of a solution activator ( a knockout ) .Of two factors obtained 9 kind of combination those who each experienced remedial treatment as much as two times order to obtain 18 unit treatment. The best treatment in this research was naoh 15 % that can be seen from the results of the parameter levels of carbon bound and absorption capacity iod more better than other treatment